Test of four hypotheses to explain the function of overmarking in foals of four equid species - Pluháček, Jan; Tučková, Vladimíra; King, Sarah R B; Šárová, Radka (Animal cognition, 2019)
Overmarking occurs when one individual places its scent mark directly on top of the scent mark of another individual. Although it is almost ubiquitous among terrestrial mammals, we know little about the function of overmarking. In addition, almost all studies on mammalian overmarking behaviour dealt with adult individuals. Reports on this behaviour in juveniles are extremely rare, yet may elucidate the function of this behaviour. We tested four mutually non-exclusive hypotheses which might explain this behaviour in juveniles: (1) conceal the individual's scent identity, (2) announcement of association with other group members, especially the mother-i.e., sharing identity with the mother, (3) to prevent the next conception of the mother, i.e., parent-offspring conflict, and (4) an early expression of male sexual behaviour. We observed 43 foals (out of 108 individuals) from all African equid species (Equus africanus, E. grevyi, E. quagga, E. zebra) in five zoos. In total, we recorded 3340 eliminations; 260 of these events were overmarked by 38 individual foals representing all species. This represents one of the highest rates of overmarking ever recorded by mammalian juveniles. Foals of all species except African wild ass overmarked the mother more often than another herdmate: with male foals overmarked at a higher rate than female foals. Mothers preferred to overmark foals, but not exclusively their own foal. Our results provide support for the hypotheses that overmarking serves to share identity between foal and mother, and that it is an early expression of male sexual behaviour.
Keywords: koně; Odorants; Mothers; Male; Pheromones; Animals; Female; mužské pohlaví; ženské pohlaví; odoranty; matky; feromony; zvířata; Horses